The Development of School Management Strategies toward Sports Excellence of Ban Nongyai Municipal School under the Office of Education, Khon Kaen Municipality - Panthaisong, Rintana (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: 1. to investigate the components and indicators for developing school management strategies toward sports excellence at Ban Nongyai Municipal School under the Office of Education, Khon Kaen Municipality; 2. to study the current conditions, desirable conditions, and needs for developing such strategies; 3. to draft the strategies for school management; and 4. to examine the results of implementing the strategies. The study was conducted in four phases. Phase 1 explored the components and indicators with seven informants using online focus group discussions. Phase 2 investigated the current and desirable conditions as well as the needs with a sample of 226 participants, including directors, deputy directors, heads of departments, sports coaches, staff, and student athletes. Phase 3 involved drafting the strategies based on best practices from five schools and verifying their appropriateness and feasibility by seven experts through online connoisseurship seminars. Phase 4 implemented the strategies with 35 participants from Ban Nongyai Municipal School. The research instruments consisted of component and indicator assessment forms, questionnaires, evaluation forms on appropriateness and feasibility, and achievement tests. Data were analyzed using percentage, mean, standard deviation, index of item-objective congruence (IOC), discrimination index, reliability coefficient, and the modified priority needs index (PNImodified). The findings revealed that: 1. the strategies comprised five components with 26 indicators, which were rated at the highest level of appropriateness; 2. the current conditions were at a moderate level, whereas the desirable conditions were at a high level, with personnel development identified as the highest need; 3. the developed strategies consisted of five main strategies, ten sub-strategies, and 40 action guidelines, with the overall appropriateness and feasibility rated at the highest level; and (4) the implementation of the strategies significantly improved participants’ knowledge at the .05 level, enhanced behavioral performance to the highest level, and achieved the highest level of satisfaction.